2021
DOI: 10.1111/anae.15626
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopy vs. direct Macintosh laryngoscopy in tracheal intubation in adults: a ranking systematic review and network meta‐analysis

Abstract: Summary Videolaryngoscopes are thought to improve glottic view and facilitate tracheal intubation compared with the Macintosh direct laryngoscope. However, we currently do not know which one would be the best choice in most patients undergoing anaesthesia. We designed this systematic review with network meta‐analyses to rank the different videolaryngoscopes and the Macintosh direct laryngoscope. We conducted searches in PubMed and a further five databases on 11 January 2021. We included randomised clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…We thank Drs Hansel and Rogers for their comments regarding our work [1]. The authors raise concerns regarding our results for percentage of glottic opening and time for intubation [2].…”
mentioning
confidence: 99%
“…We thank Drs Hansel and Rogers for their comments regarding our work [1]. The authors raise concerns regarding our results for percentage of glottic opening and time for intubation [2].…”
mentioning
confidence: 99%
“…Videolaryngoscopy has been shown to improve the glottic view and reduce the number of attempts to successful intubation in adult patients compared with direct laryngoscopy. [1][2][3] However, their benefit for children is not equally clear. Data from the Pediatric Difficult Intubation Registry (PeDIR) have shown that videolaryngoscopy with both standard and hyperangulated blades has significantly higher success rates and fewer complications when compared to direct laryngoscopy in children who are difficult to intubate.…”
Section: Introductionmentioning
confidence: 99%
“…Other systematic reviews evaluating infants and older children have not found significant differences between videolaryngoscopy and direct laryngoscopy for a range of intubation‐related outcomes 9–11 . Recent studies have demonstrated that different videolaryngoscope blade designs may influence their performance 1,2,6 . Evaluating videolaryngoscopes as a single intervention may contribute to the lack of significant difference in most pairwise analyses available in children.…”
Section: Introductionmentioning
confidence: 99%
“…We enjoyed reading the ranking systematic review and network meta-analysis by de Carvalho et al [1]. Randomised…”
mentioning
confidence: 99%
“…We enjoyed reading the ranking systematic review and network meta‐analysis by de Carvalho et al [1]. Randomised controlled trials comparing videolaryngoscopes have blossomed over the past 5 years since the publication of the last Cochrane review by Lewis et al [2] on the topic, and an updated summary of the evidence is indeed overdue.…”
mentioning
confidence: 99%